Antioxidant activity of Halamphora coffeaeformis: a fucoxanthin-producing microalga with potential health benefits - Bauchi, Ana Victoria (2023)
Fucoxanthin (Fx) is a major photosynthetic light-harvesting carotenoid found in diatoms and brown seaweeds, presenting numerous beneficial properties for health, such as antioxidant, hypoglycemic, antimicrobial, anti-obesity, anti-aging anti-metastatic, among others. We carried out previous studies with cultures of the marine diatom Halamphora coffeaeformis, isolated from the Bahía Blanca Estuary (Argentina), evidencing a significant Fx production. The aim of this work was to evaluate the antioxidant capacity of H. coffeaeformis extracts by implementing an optimized protocol for 2,2’-Azino-bis(3-ethylbenzthiazoline-6-sulfonic acid) diammonium salt radical (ABTS•+) bleaching test. Cultures were performed in duplicate in Erlenmeyers with f/2 medium at 33‰, and with a light:dark photoperiod of 12 h:12 h, adapted to a photosynthetically active radiation intensity of 100 μE m-2 s-1. Antioxidant activity was determined by a Jasco V-630 UV-Vis spectrophotometer by ABTS•+ scavenging activity measurement after the addition of Fx enriched culture extracts. The obtained results showed that ABTS•+ discoloration assay is an efficient antioxidant activity indicator of H. coffeaeformis´extracts, demonstrating for concentrations less than 0,01 mg mL-1, similar ABTS•+ bleaching results than ascorbic acid, used as a reference positive control. Fx and associated pigment production during the stationary growth phase in cultures were evidenced by HPLC chromatography. H. coffeaeformis cultures under studied conditions showed strong antioxidant properties, with the effective concentration for 50% scavenging (EC50) of ABTS•+ being 0,02 mg mL-1. In conclusion, the obtained results suggested that H. coffeaeformis is a sustainable Fx source, encouraging future studies of its bioactive properties in health.